Effect of controlled atmospheres with low oxygen levels on extended storage of Guava Fruit (Psidium guajava L. 'Pedro Sato') - Teixeira, Gustavo H.A. [UNESP]; Durigan, José F. [UNESP] (American Society for Horticultural Science, 2010)
The effects of controlled atmospheres (CAs) containing different levels of oxygen (air, 21, 15, 10, 5, and 1 kPa) were investigated during cold storage of 'Pedro Sato' guava at 12.5 8C for 28 days. Atmospheres with lower O2 concentrations (1 and 5 kPa) significantly reduced respiratory rates and delayed the ripening process. This was confirmed by maintenance of fruit green color, higher total soluble, and reducing sugar contents. The control fruits and those stored in elevated oxygen concentrations (21 kPa) presented a climacteric peak. However, the peak was not observed for fruit maintained in atmospheres containing 1, 5, 10, and 15 kPaO2. After transferring the fruits from CA to ambient storage, they ripened normally in just 2 d without presenting any low O2 injury symptoms, even from the lowest oxygen concentrations (1 and 5 kPaO2). This supports the use of low-oxygen atmospheres for extended storage of 'Pedro Sato' guava fruit.
Keywords: Pectin; Respiration; Ripening; Shelf life; Softening; Yellowing